THE INFLUENCE OF BRAND IMAGE, CONTENT MARKETING, AND STORE TRUST ON PURCHASE DECISIONS: CASE STUDY ON TIKTOK APP USER CONSUMERS - M. Rizki; Kussudyarsana Kussudyarsana (Komitmen: Jurnal Ilmiah Manajemen, 2023)
Tiktok is one of the several online shopping applications created as a result of the advent of the internet. This study attempts to identify the impact of shop trust, content marketing, and brand perception on Tiktok purchasing decisions. Purposive sampling is used in this quantitative research method, which collects data from a sample of 100 respondents using a questionnaire. Multiple regression to analyze data. The study's findings show that while content marketing has a favorable and significant impact on buying behavior with sig. value 0.000, brand image has no discernible influence with a sig value of 0.395. With a sig value of 0.000, shop trust has a favorable and significant impact on purchasing decisions. Brand image, content marketing, and shop trust all have an impact on purchasing choices at the same time or simultaneously influence.